The Effectiveness of the Public Aspiration Process in Decision-Making in the Education Sector in the DPRD of North Bolaang Mongondow Regency - Tia Aprilia Modanggu; Ansar Ansar; Arifin Suking (Darul Yasin Al Sys, 2026)
This study is motivated by the suboptimal use of public aspirations in decision-making processes within the Regional House of Representatives (DPRD), particularly in relation to weak management, documentation, follow-up mechanisms, and alignment with regional development priorities. This study aims to analyze the collection of public aspirations, their institutional processing within the DPRD, and their utilization in decision-making in the DPRD of North Bolaang Mongondow Regency. A qualitative approach with a case study design was employed. Research informants were selected purposively and consisted of the DPRD chairperson, commission leaders, DPRD secretariat staff, and community leaders. Data were collected through in-depth interviews, participatory observation, and documentation studies, and were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, and conclusion drawing. The findings indicate that public aspirations are collected through recess activities, working visits, audiences, public hearings (RDP), and Musrenbang, with recess serving as the dominant mechanism. The processing of aspirations involves recording, classification, verification, commission-level discussions, and the preparation of policy recommendations. Public aspirations are then utilized in the formulation of development programs, budgeting, policy monitoring, and public service evaluation. However, their effective use continues to face several obstacles, including weak system digitalization, limited documentation, low inclusive public participation, and constrained regional budgets. The study concludes that the effectiveness of public aspiration utilization is strongly influenced by the institutional capacity of the DPRD to manage, prioritize, and follow up on public inputs. The implications of this study emphasize the need to develop an e-aspiration system, improve transparency in aspiration follow-up, and strengthen public participation to support participatory, responsive, and accountable regional governance.